Using the Moodle System - Hamroyev Rustam Rasulovich (Zien Journals, 2022)
This article discusses the development of information technology and the increasing flow of information, the rapidly changing data and the human need to find new ways to process this information in a timely manner.
Keywords: education system; information and communication; technologies distance learning